2012
DOI: 10.18869/acadpub.johe.1.3.139
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Malnutrition among Children under 5 Years old Referred to Health Centers in Iranshahr during 2010-2011

Abstract: Background: Malnutrition is steel a major health problem in the developing countries. It is recognized that 60% of death among children fewer than five years in these countries are associated with malnutrition. The aim of this study was to estimate the prevalence of malnutrition in children under 5 years old in Iranshahr in 2011. Materials and Methods: This is a cross-sectional descriptive study. The sample consisted of 700 children less than 5 years old were randomly selected by cluster and quota method among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…[16] Iraq Multiple Indicator Cluster Survey (MICS-4) in 2011 found that 8% of under-five children were moderately or severely underweight, and 4% of them were severely underweight. [17] The results of the current study showed that the prevalence of under-nutrition was 19.2% measured by BMI and 19.5% measured by MAC. This prevalence is considered high when compared to the regional communities like Iran in which the prevalence of malnutrition was found to be 11.1% and of wasting was 7.2%, [18] or other countries like Nepal where the prevalence of malnutrition was 18.9% and 7% wasting.…”
Section: Discussionmentioning
confidence: 52%
“…[16] Iraq Multiple Indicator Cluster Survey (MICS-4) in 2011 found that 8% of under-five children were moderately or severely underweight, and 4% of them were severely underweight. [17] The results of the current study showed that the prevalence of under-nutrition was 19.2% measured by BMI and 19.5% measured by MAC. This prevalence is considered high when compared to the regional communities like Iran in which the prevalence of malnutrition was found to be 11.1% and of wasting was 7.2%, [18] or other countries like Nepal where the prevalence of malnutrition was 18.9% and 7% wasting.…”
Section: Discussionmentioning
confidence: 52%
“…In the next stage and after evaluating the full text of the articles, 26 articles were excluded (7 review articles, 10 low-quality articles and 9 articles with insufficient data). Finally, after a thorough review of the articles, 27 articles from 2002 to 2016 were selected to enter the meta-analysis stage [111213141516171819202122232425262728293031323334353637] (Figure 1). The general specifications and data of these articles are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, a common characteristic of all recent studies conducted in Iran on malnutrition among under-5 children is that they have all studied the prevalence of malnutrition in a particular period or its trend over time [ 12 - 14 ]. Since malnutrition is a complicated phenomenon, for which socioeconomic factors such as the educational level of the parents as well as household income are relevant [ 16 - 18 ], it shows large disparities among socioeconomic groups [ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%